2014
DOI: 10.1177/0192513x14536565
|View full text |Cite
|
Sign up to set email alerts
|

Circle of Care

Abstract: In the contemporary family, which is increasingly shaped by multicultural influences, parents rarely are the sole caretakers of their children. To improve understanding of family dynamics, researchers must redefine caregiving networks to include multiple caregivers, such as extended family members. This study explored the influences of caregiving networks on youth depression by examining who youths perceived as caretakers, how many caretakers were in their networks, the youths’ connectedness with adults in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Today, empirical support exists for more expansive family networks among families of color. For instance, studies have found that Black and Hispanic children are more deeply embedded in their extended families than White children, spending more time with extended family members and receiving from them greater emotional and practical support (Cross, 2020;Margolis et al, 2014). There are clear benefits of adopting pedi-focal definitions of family, particularly in complex family structures.…”
Section: Defining Family Formsmentioning
confidence: 99%
“…Today, empirical support exists for more expansive family networks among families of color. For instance, studies have found that Black and Hispanic children are more deeply embedded in their extended families than White children, spending more time with extended family members and receiving from them greater emotional and practical support (Cross, 2020;Margolis et al, 2014). There are clear benefits of adopting pedi-focal definitions of family, particularly in complex family structures.…”
Section: Defining Family Formsmentioning
confidence: 99%
“…Among these three subgroups, the “stable disconnected” group had the highest levels of adolescent-reported behavior problems and depression. This subgroup may be the highest risk in terms of promoting adolescent disengagement from the family, placing adolescents at risk for feelings of isolation, and may provide greater opportunity for engaging in problem behaviors without adequate parental guidance and supervision (Dishion et al, 2004; Fosco et al, 2012; Margolis et al, 2016). It is less clear whether these subgroups reflect different family “types” or a developmental progression (e.g., parent disengages first, then both).…”
Section: Discussionmentioning
confidence: 99%
“…Parent-adolescent connectedness – feelings of closeness, trust, and support – is a protective factor against substance use, antisocial behavior, depression, suicidal ideation, and poor self-esteem (Ackard, Neumark-Sztainer, Story, & Perry, 2006; Fosco, Stormshak, Dishion, & Winter, 2012; Margolis, Fosco, & Stormshak, 2016). Adolescents who are more connected to their parents are more likely to seek out guidance as they navigate difficulties (e.g., with peers or at school; Ackard et al, 2006); however adolescents who feel less connected with their parents may disengage from the family and become isolated and depressed, or engage in problem behavior while away from home and unsupervised (Fosco & LoBraico, in press).…”
mentioning
confidence: 99%
“…The caregiver landscape can be successfully supported through tailored solutions by acknowledging their unique challenges. Caregivers are largely invisible and are mostly underappreciated resources in community health services [ 2 , 3 ]. Caregivers are vital partners who contribute to health care provisioning in communities.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of this important contribution to health care delivery, caregivers receive minimal support from governments [ 7 , 8 ]. Globally, caregivers share a myriad of ongoing challenges and obstacles that are burdensome [ 2 , 9 ], often leading to unmet physical, psychological, and financial needs [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%